The protective effects of S14G-humanin (HNG) against mono-sodium urate (MSU) crystals- induced gouty arthritis. Issue 1 (1st January 2022) - Zhang, Jihui; Lei, Hongwei; Li, Xiu
ABSTRACT: Gout is a common and complex form of arthritis that has brought great inconveniences to the normal lives of patients. It is reported that oxidative stress and nod-like receptor family protein 3 (NLRP3) inflammasome-mediated inflammatory reactions are involved in the pathogenesis of gout arthritis. S14G-humanin (S14G-HNG) is a modified peptide of HNG with higher inhibitory activity on the accumulation and deposition of Aβ. Recently, S14G-HNG has been reported to exert great anti-inflammatory effects. The present study proposed to explore the possible therapeutic property of S14G-HNG against gout arthritis. An animal model was established by stimulation with mono-sodium urate (MSU) crystals, followed by treatment with colchicine and S14G-HNG, respectively. The elevated Gait score promoted synovitis score and activated myeloperoxidase (MPO) observed in MSU crystals-treated mice were significantly reversed by colchicine and S14G-HNG. Bone marrow-derived macrophages (BMDMs) were isolated from mice and stimulated with MSU crystals, followed by being treated with 25 and 50 μM S14G-HNG. The increased mitochondrial reactive oxygen species (ROS) and Malondialdehyde (MDA) levels, upregulated NADPH oxidase-4 (NOX-4), activated NLRP3 inflammasome, and elevated production of inflammatory factors in MSU crystals-treated BMDMs were dramatically reversed by S14G-HNG, accompanied by the upregulation of sirtuin type-1 (SIRT1). Lastly, the protective effects of S14G-HNG against MSU crystals-induced NLRP3 inflammasome activation were significantly abolished by the knockdown of SIRT1. In conclusion, our data reveal that S14G-HNG could possess potential benefits against MSU crystals-induced gout arthritis, with colchicine displaying a better effect.